Examining the STEM-Science Achievement Test (SSAT) Using Rasch Dichotomous Measurement Model - Jamaludin, J.; Lay, Y. F.; Khoo, C. H.; Leong, A. S. Y. (Jurnal Pendidikan IPA Indonesia, 2021)
The main purpose of this study is to develop a valid and reliable instrument to measure the STEM-Science achievement of primary school students in Malaysia. Six Year 4 Science topics (Scientific Skills, Life Processes of Human, Properties of Materials, Measurement, Solar System, Importance of Technologies in Life) and Six Year 5 Science topics (Rules and Regulation in Science Lab, Life Processes of Plants, Acids and alkali, Electricity, Earth and Space Science, Technology and Sustainable Life) have been included in the development of the STEM-Science Achievement Test (SSAT). 226 Year 4 and 226 Year 5 primary school students in Sabah responded to the developed instrument to test their STEM-Science knowledge. The Rasch dichotomous measurement model approach was used to evaluate the validity and reliability of the SSAT. The validity assessed the Point-Measure Correlation (PTMEA CORR), Principal Component Analysis of Residuals (PCAR), as well as Infit and Outfit Mean Squares (MNSQ). In terms of reliability, Cronbach’s alpha, item reliability, and item separation index were analysed. The analysis results revealed the presence of unidimensionality for both objective and subjective items. For objective items, the reported values for Cronbach’s Alpha are .81 and .83; item reliability are .95 and .95; item separation are 4.21 and 4.25 for Year 4 and Year 5 students, respectively. Standardised residual correlations for Year 4 and Year 5 subjective items also showed satisfactory values. The assessment using Rasch measurement model has proven that SSAT is a valid and reliable instrument to measure Malaysian primary students’ STEM-Science-related knowledge.